Green lacewings (Neuroptera: Chrysopidae) associated with Melon Crop in Mossoró, Rio Grande do Norte State, Brazil - Bezerra, Carlos E S; Tavares, Patrícia K A; Macedo, Luciano P M; Freitas, Sérgio de [UNESP]; Araujo, Elton L (Sociedade Entomológica do Brasil, 2010)
A survey of the green lacewings associated with the melon agroecosystem was carried out with the aim of including lacewings into the integrated management program of melon pests. Three species of this predator were found: Ceraeochrysa cubana (Hagen), Chrysoperla externa (Hagen) and Chrysoperla genanigra Freitas. A key to these species is presented.
Keywords: Semiarid; predator; Chrysoperla; Ceraeochrysa